ANALISIS PENERAPAN SISTEM ANTRIAN PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR CABANG PEMBANTU UNIT PALLANGGA KABUPATEN GOWA - Maghfirah Maghfirah; Moh Aris Pasigai; Muhammad Nur Abdi (Jurnal Ilmu Manajemen Profitability, 2019)
This study aims to determine the application of the customer queue system that is currently used in the transaction process at PT. Bank Rakyat Indonesia (Persero) Tbk. Pallangga Unit Branch Office of Gowa Regency. The type of research used in this research is descriptive quantitative. The processed data is the arrival of customers who make transactions on the teller's part in PT. Bank Rakyat Indonesia (Persero) Tbk. Pallangga District Branch Office of Gowa Regency While the data analysis technique used in the research is to analyze the number of customers using the M / M / s queue line (Multiple Channel Query System) using 2 tellers that are currently applied to PT. Bank Rakyat Indonesia (Persero) Tbk. The Pallangga Unit Branch Office of Gowa Regency then analyzed by adding the number of tellers (services). Then compare the results of time efficiency calculations and service optimization. The results of the data study indicate that the system of implementing the queuing system will be optimal according to service time standards when adding 1 number of tellers (services) to 3 tellers to serve customers so that the overall operational performance is not disrupted and the transaction process can run optimally so as not to cause customers long.